2012
DOI: 10.1177/0148607112445580
|View full text |Cite
|
Sign up to set email alerts
|

Jonathan E. Rhoads Lecture 2011

Abstract: This lecture reviews the current understanding of how insulin resistance, as a marker of the metabolic stress, is involved in recovery after major surgery. Insulin resistance develops as a graded response related to the magnitude of the operation. It lasts for weeks after medium-size surgery and affects all parts of body metabolism. Although hyperglycemia develops, muscle and fat uptake is reduced and other non-insulin-sensitive cells have an increase in glucose uptake as a result of the elevated glucose level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 157 publications
(44 citation statements)
references
References 66 publications
0
43
0
1
Order By: Relevance
“…The physiology behind the improvements gained by the ERAS protocol is believed to be stress reduction [13]. The current data suggest that the same benefit from the ERAS program should be expected in patients with malignant disease.…”
Section: Discussionmentioning
confidence: 84%
“…The physiology behind the improvements gained by the ERAS protocol is believed to be stress reduction [13]. The current data suggest that the same benefit from the ERAS program should be expected in patients with malignant disease.…”
Section: Discussionmentioning
confidence: 84%
“…This concept not only applies to physiological/metabolic changes but also to changes in the innate immune system. This combination of catecholamine release and hyper‐inflammation followed by immunosuppression can contribute, among other things, to a state of insulin resistance 19, 20…”
Section: Why It Is Important To Control Surgical Stress and Maintain mentioning
confidence: 99%
“…Any major injury including surgery disrupts metabolic homoeostasis and cause insulin resistance. Insulin resistance can be defined as a condition, whereby a normal concentration of insulin produces a subnormal biological response 19. Studies have demonstrated a significant correlation between the degree of the patient's insulin sensitivity on the first post‐operative day and length of hospital stay ( r  = 0.53, P  = 0.0001) 20.…”
Section: Metabolic Homoeostasismentioning
confidence: 99%
“…One of the most important metabolic reactions during surgery is resistance to insulin and hyperglycemia [1]. Hyperglycemia in the perioperative period is due to stress hormones such as epinephrine, cortisol, and inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%